Sexual experiences among multicultural adolescents in Korea: evidence from the Korean Youth’s Risk Behavior Survey - Kim, Keuntae; Jo, Se Hee (Frontiers in Sociology, 2024)
Several studies have examined adolescent sexual behaviors by family immigration status, but most of these failed to account for heterogeneity within youths' multicultural backgrounds. To fill this gap in the literature, this paper draws data from the 2011 to 2022 rounds of the Korean Youth's Risk Behavior Survey (N = 769,160) and compares the likelihood of sexual intercourse across four groups of adolescents. Results from logistic regression indicate that the odds of having sexual contact increased 2.8 times for youths with a non-Korean father and Korean mother, compared with those from families with two Korean parents. When both father and mother are foreign-born, the odds of being sexually active increased 4.7 times. In both cases, the discrepancies might be primarily associated with the foreign fathers' lack of socioeconomic resources. Therefore, the father's role deserves more examination, and sex education in schools should be tailored to reflect multicultural adolescents' needs.